Central War Archive Documents about the Repression against Military Officers of Polish Army in 1944–1956 - Roman, Wanda Krystyna (Genocidas ir rezistencija, 1997)
The Polish army was a very important element influencing the country’s domestic situation and, to some extent, its foreign policy. The government of the People’s Republic of Poland did not hesitate to use the army to support the anti–democratic political system. The Communist Party had complete control over the Polish army, which was one of the most important elements on which the Party based its power. The army was supposed to suppress political forces hostile to the regime, and it did so. It was therefore necessary first to remove undesirable elements from its ranks. There was no place in the Polish army for officers and soldiers whose military background was not linked to left–wing organisations.